The Causal Significance of Organizational Climate, Work Ecosystem, and Staffing Regulatory Framework on With-drawal Behavior: (A Study at Pt Bank Mandiri (Persero) Pati) - Aditya Angger Wibowo (International Journal of Economics, Management and Accounting, 2026)
This study aims to examine the influence of organizational climate, work ecosystem, and staffing regulatory framework on employee withdrawal behavior at PT Bank Mandiri (Persero) Tbk, Pati Branch Office. This research employed a quantitative approach using digital questionnaires distributed through Google Form to 60 active employees as respondents. The collected data were analyzed using inferential statistical methods, including partial and simultaneous regression analysis, to identify the causal relationships among variables. Withdrawal behavior was measured through indicators of psychological and physical disengagement tendencies, while organizational climate, work ecosystem, and staffing regulatory framework were used as independent variables. The results show that organizational climate has no negative and statistically significant effect on withdrawal behavior, indicating that internal climate stability does not necessarily reduce employees’ withdrawal tendencies. Meanwhile, work ecosystem and staffing regulatory framework partially have a positive and significant influence on increasing withdrawal behavior. Simultaneously, the three variables significantly contribute to predicting employee withdrawal behavior. These findings indicate that excessive formal regulations and an unbalanced work environment may increase employee disengagement. Therefore, management is encouraged to strengthen human capital strategies through fair reward systems, performance recognition, and improved organizational support to enhance employee retention and reduce turnover-related costs.